Method for producing biodegradable polymer composite and biodegradable polymer composite
In-situ polymerization of PBAT with organic fillers addresses compatibility issues, resulting in biodegradable polymer complexes with improved mechanical properties and controlled biodegradability, achieved through uniform filler distribution and optimized reaction conditions.
Patent Information
- Application Number
- JP2023521788
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-25
- Filing Date
- 2021-10-26
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2041-10-26
AI Technical Summary
Existing biodegradable polymers like PBAT and PLA face compatibility issues when blended, requiring additional compatibility agents and physical mixing, which limits the distribution of organic fillers and often results in overuse, leading to inefficiencies and increased costs.
A method involving the in-situ polymerization of PBAT with organic fillers, where a catalyst mixture is first prepared with the fillers, ensuring uniform distribution, followed by esterification and polymerization to create a biodegradable polymer composite with improved mechanical properties.
The method produces biodegradable polymer complexes with enhanced mechanical properties and biodegradability, achieving high efficiency and low costs without the need for post-processing, and allows for controlled crystallinity and biodegradation rates.
Smart Images

Figure 0007625326000001 
Figure 0007625326000002
Abstract
Description
[Technical field]
[0001] The present specification relates to a method for producing a biodegradable polymer composite having excellent mechanical properties, and to a biodegradable polymer composite having excellent mechanical properties. [Background technology]
[0002] Polyester resins have excellent mechanical and chemical properties and are being used in a variety of applications, such as drinking water containers, medical applications, food packaging paper, food containers, sheets, films, and automotive molded products.
[0003] Among them, polybutylene adipate terephthalate (PBAT) is a soft polyester that is biodegradable, and is therefore in the spotlight as a substitute for polyolefin polymers, which are mainly used in packaging materials and agricultural films due to recent environmental regulations.
[0004] However, since the mechanical properties of soft PBAT are somewhat insufficient for use alone in this application, it is mainly used in a blend with hard polylactic acid (PLA) or in a compound with an organic filler such as carbon black.
[0005] However, when blended with PLA, the biodegradability is lower than when PBAT is used alone, and since PBAT and PLA are not compatible, a compatibilizer must be added. Also, when using PBAT alone to compound with organic fillers, mixing using an extruder is used. This type of physical mixing has limitations in dispersing the organic filler, and in many cases an excess amount is added compared to the actual amount required, so it is common to create a masterbatch with a high organic filler content and mix it. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides a biodegradable polymer composite having excellent mechanical properties and a method for producing a biodegradable polymer composite having excellent mechanical properties. [Means for solving the problem]
[0007] In one embodiment of the present invention, a method for producing an organic filler and polybutylene adipate terephthalate (PBAT) is provided, comprising preparing a catalyst mixture in the presence of the organic filler and then introducing the catalyst mixture into a polymerization system.
[0008] In another embodiment of the present invention, there is provided a biodegradable polymer composite comprising: polybutylene adipate terephthalate; and an organic filler dispersed among polymer chains of the polybutylene adipate terephthalate. Effect of the Invention
[0009] According to the manufacturing method of the embodiment, a biodegradable polymer composite having excellent mechanical properties even when used alone can be provided efficiently and at low cost without performing any post-processing.
[0010] In addition, the biodegradable polymer composite of the embodiment has a crystallinity controlled according to the content of the organic filler, and has excellent biodegradability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates a different meaning. In this specification, the terms "include", "comprise", "have" or "have" are intended to specify the presence of an embodied feature, number, step, component, or combination thereof, and should be understood as not precluding the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0012] Since the present invention can be modified in various ways and can have various forms, specific embodiments are exemplified and described in detail below. However, this is not intended to limit the present invention to the specific disclosed form, and it should be understood that the present invention includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.
[0013] Hereinafter, an embodiment of the present invention will be described in detail.
[0014] Method for producing biodegradable polymer composites According to one embodiment of the present invention, there is provided a method for producing a biodegradable polymer composite, the method including the steps of: preparing a monomer mixture including adipic acid and terephthalic acid; mixing an organic filler, 1,4-butanediol, and a catalyst to prepare a catalyst mixture; and mixing the monomer mixture and the catalyst mixture to perform an esterification reaction.
[0015] According to the manufacturing method of the embodiment, polybutylene adipate terephthalate composited with an organic filler by in-situ polymerization can be provided, which can exhibit sufficient physical properties even when used alone.
[0016] Therefore, unlike polybutylene adipate terephthalate polymerized in an environment in which no organic filler is present, the manufacturing method of the embodiment can provide a biodegradable polymer composite with improved biodegradability while exhibiting sufficient physical properties even when used alone without performing post-processing, with high efficiency and low cost.
[0017] Here, the biodegradable polymer composite is one in which an organic filler is dispersed among the polymer chains of polybutylene adipate terephthalate, and is distinguished from a blend resin in which a liquid or solid polybutylene adipate terephthalate polymer resin composition and an organic filler are simply mixed.
[0018] Hereinafter, in some cases, the "biodegradable polymer composite" may be abbreviated to simply "complex."
[0019] Catalyst mixture preparation process In the process of preparing the catalyst mixture, 1,4-butanediol and a catalyst are mixed with an organic filler to prepare the catalyst mixture. This process allows the catalyst mixture in which the organic filler is uniformly dispersed to be supplied to the polymerization system.
[0020] When such organic fillers are polymerized together with polymers such as PBAT, the organic fillers must be uniformly dispersed among the newly formed polymer chains in order to effectively improve the physical properties.
[0021] In one embodiment of the present invention, a catalyst mixture is prepared by reacting an organic filler such as cellulose with a catalyst in advance, and then the catalyst mixture thus prepared is added to a polymerization reaction. In this case, the organic filler can be more uniformly dispersed during the formation of PBAT polymer chains than when the polymerization reactants, polymerization catalyst, and organic filler are added simultaneously.
[0022] According to one embodiment of the method of the present invention, the catalyst is distributed on the surface of the organic filler by premixing the organic filler with the catalyst material. More specifically, an ester exchange reaction occurs between various functional groups contained in the organic filler molecule and the catalyst molecule, and such an ester exchange reaction is restricted to some extent by the steric hindrance of the organic filler molecule, so that a catalyst-organic filler complex in the form of the catalyst molecule coating the surface of the organic filler can be formed.
[0023] In general, organic fillers can cause aggregation between organic filler molecules due to the functional groups in the molecule and their shapes, but according to one example of the method of the present invention, as described above, the surface of the organic filler is coated with catalyst molecules, which can prevent the organic filler molecules from overlapping or agglomerating with each other. Due to this principle, the organic filler molecules are dispersed with each other, and the organic filler can be more uniformly dispersed in the polymer during the polymerization process in which PBAT polymer chains are formed.
[0024] Therefore, as the polymerization reaction progresses, the polymer chains grow from the surface of the organic filler, so that the organic filler can be uniformly distributed among the polymer chains to such an extent that the polymer chains and the organic filler are not separated from each other.
[0025] Furthermore, according to this method, the organic filler is uniformly dispersed among the polymer chains, preventing the polymer chains from crystallizing, and a polymer composite having a low degree of crystallinity can be produced.
[0026] In addition, in this process, some of the catalyst clusters can be broken down in advance to increase the number of reaction sites, producing a partially activated catalyst. By supplying such a partially activated catalyst, the initial reaction rate of the polymerization system can be increased and the polymerization time can be reduced.
[0027] The step of preparing the catalyst mixture may be carried out at a temperature range of 40 to 240° C. for 10 to 120 minutes.
[0028] Within the above temperature and time ranges, a catalyst mixture in which the organic filler is uniformly dispersed can be prepared, the catalyst clusters are broken to generate a maximum number of reaction sites, and the catalyst is coated on the surface of the organic filler to appropriately mediate the polymerization reaction of the monomer and the prepolymer described below.
[0029] However, excessively low temperatures during preparation of the catalyst mixture can reduce the dispersion of the organic filler and crystallize the 1,4-butanediol, leading to miscibility and / or reactivity problems, whereas excessively high temperatures during preparation of the catalyst mixture can reduce the thermal stability of the catalyst and lead to discoloration of the final PBAT.
[0030] On the other hand, if the preparation time of the catalyst mixture is too short, the activation will be insufficient, and if the preparation time of the catalyst mixture is too long, polymerization of 1,4-butanediol may occur or discoloration of the final PBAT may occur.
[0031] In consideration of such tendency, the temperature during preparation of the catalytic mixture may be adjusted. For example, the step of preparing the catalytic mixture may be performed at a temperature range of 40° C. or more, 50° C. or more, 60° C. or more, or 70° C. or more, and 240° C. or less, 200° C. or less, 140° C. or less, or 90° C. or less. Also, the step may be performed within a time range of 10 minutes or more, 15 minutes or more, 20 minutes or more, or 25 minutes or more, and 120 minutes or less, 90 minutes or less, 60 minutes or less, or 40 minutes or less.
[0032] The catalyst in the catalyst mixture may be included in an amount of 0.001 to 10 parts by weight based on 100 parts by weight of adipic acid in the monomer mixture.
[0033] Within this range, the esterification reaction of the monomer mixture and the polymerization of the esterification reaction product (ie, prepolymer) can be adequately mediated.
[0034] However, if the amount of catalyst added during the preparation of the catalyst mixture is too small, the polymerization time will be long and the productivity will decrease.In contrast, if the amount of catalyst added is too large, the polymerization time will be short, but the possibility of discoloration of the final PBAT will increase, so the amount of heat stabilizer added must be increased in proportion to the amount of catalyst added, which increases the production cost.
[0035] Considering such a tendency, the amount of catalyst in the catalyst mixture can be adjusted. For example, the catalyst in the catalyst mixture can be used in an amount of 0.001 parts by weight or more, 0.005 parts by weight or more, or 0.01 parts by weight or more, and 10 parts by weight or less, 5 parts by weight or less, or 0.1 parts by weight or less, based on 100 parts by weight of adipic acid in the monomer mixture.
[0036] The organic filler in the catalyst mixture may be present in an amount of 0.5 to 20 g, or 1.0 to 20 g, or 1.5 to 17 g, or 1.5 to 5 g, or 1.5 to 3 g per mmol of the catalyst.
[0037] Within this range, the reinforcing effect of the organic filler and the reaction mediating effect of the catalyst can be balanced.
[0038] However, if the amount of organic filler added is too low compared to the catalyst, the reinforcing effect due to the interaction between the organic filler and the catalyst described above will be insufficient, and if the amount of organic filler added is too high, uneven dispersion will occur, which may result in a decrease in catalyst activity.
[0039] Meanwhile, the amount of 1,4-butanediol in the catalyst mixture may be 150 to 250 parts by weight based on 100 parts by weight of adipic acid in the monomer mixture.
[0040] This is the total amount of 1,4-butanediol required for the synthesis of PBAT. 1,4-butanediol is a reactant and can also function as a solvent or dispersant for dispersing an organic filler. In conventional methods, in order to ensure uniformity and stability of the catalyst during polymerization, only a portion of the 1,4-butanediol to be reacted is often supplied, and the remaining amount is supplied during a future reaction. However, in a manufacturing method according to an embodiment of the present invention, the entire amount of 1,4-butanediol to be reacted is supplied to the catalyst mixture, thereby increasing the dispersibility of the organic filler, which will be described later.
[0041] From this viewpoint, the amount of 1,4-butanediol in the catalyst mixture may be 150 to 250 parts by weight based on 100 parts by weight of adipic acid in the monomer mixture.
[0042] For example, the amount of 1,4-butanediol in the catalyst mixture may be 180 to 220 parts by weight based on 100 parts by weight of adipic acid in the monomer mixture.
[0043] The organic filler is not particularly limited as long as it is widely used as a polymer reinforcing material in the technical field to which the present invention pertains.
[0044] Specifically, the organic filler may be a cellulose or starch-based compound, and the cellulose or starch-based compound may be substituted with an alkyl group, a hydroxyl group, a carboxyl group, a hydroxyalkyl group, a carboxyalkyl group, or the like.
[0045] The catalyst is not particularly limited as long as it is widely used as a polyester polymerization catalyst in the technical field to which the present invention pertains.
[0046] Specifically, the catalyst may be at least one selected from the group consisting of titanium methoxide, titanium ethoxide, titanium propoxide, titanium isopropoxide, titanium butoxide, and titanium isobutoxide.
[0047] For example, the catalyst can be titanium butoxide.
[0048] Prepolymer manufacturing process The prepolymer refers to a polymer with a relatively low degree of polymerization, the polymerization reaction of which is stopped midway in order to facilitate molding.
[0049] In one embodiment, the prepolymer corresponds to a polymer having a relatively low degree of polymerization produced by esterifying a monomer mixture including adipic acid and terephthalic acid in the presence of the catalyst mixture.
[0050] According to an embodiment of the present invention, in the process of forming the prepolymer, initial polymer chains may be formed around the surface of the organic filler, with the catalyst being coated on the surface of the organic filler as the center.
[0051] Specifically, the monomer mixture may contain 50 to 150 parts by weight of the terephthalic acid based on 100 parts by weight of the adipic acid in the monomer mixture.
[0052] Terephthalic acid may affect the crystallinity of the polymer due to the aromatic ring structure, but the polymer produced within the above range of addition can have excellent mechanical properties and biodegradability.
[0053] For example, the monomer mixture may contain 80 to 120 parts by weight of the terephthalic acid based on 100 parts by weight of the adipic acid in the monomer mixture.
[0054] In the step of preparing the prepolymer, 0.1 to 1 part by weight of a crosslinking agent or branching agent can be added based on 100 parts by weight of adipic acid in the monomer mixture to carry out an esterification reaction.
[0055] When a crosslinking agent is added and an esterification reaction is carried out, an internally crosslinked prepolymer is produced, which can improve the mechanical properties of the final composite.
[0056] The crosslinking agent can be a low molecular weight compound containing three or more hydroxy groups or three or more carboxy groups in the molecule, such as glycerol or citric acid. For example, the crosslinking agent can be glycerol.
[0057] The step of preparing the prepolymer may be carried out at a temperature range of 150 to 350° C. for 10 to 120 minutes.
[0058] Within the above temperature and time ranges, the prepolymer can be produced while maintaining uniform dispersion of the organic filler.
[0059] For example, the step of preparing the prepolymer may be performed at a temperature of 150° C. or more, 170° C. or more, 190° C. or more, or 210° C. or more, and 350° C. or less, 320° C. or less, 290° C. or less, or 250° C. or less, and for a time period of 10 minutes or more, 15 minutes or more, 20 minutes or more, or 25 minutes or more, and 120 minutes or less, 90 minutes or less, 60 minutes or less, or 40 minutes or less.
[0060] Nitrogen gas can be injected during the step of preparing the prepolymer. Specifically, when nitrogen gas is injected, water generated as a by-product can be quickly removed, thereby suppressing reverse reactions caused by water and increasing the conversion rate and molecular weight of the monomer.
[0061] For example, the nitrogen gas can be injected at a rate of at least (0.001) ml / min, at least (0.01) ml / min, at least (0.02) ml / min, or at least (0.05) ml / min, and at most (100) ml / min, at most (50) ml / min, at most (10) ml / min, or at most (5) ml / min.
[0062] During polymerization of the prepolymer, 0.001 to 10 parts by weight of a catalyst may be additionally added based on 100 parts by weight of adipic acid in the monomer mixture.
[0063] The catalyst added first is likely to lose activity during the prepolymer production stage. For example, titanium, the central metal component of the catalyst, can react with water, a by-product of the ester reaction, to form titanium oxide, and the functional groups present in the molecules of the organic filler described above can be substituted with the alkoxide sites of titanium alkoxide. Therefore, it is preferable to add additional catalyst immediately before the reaction.
[0064] For example, the additional catalyst may be used in an amount of 0.001 parts by weight or more, 0.005 parts by weight or more, or 0.01 parts by weight or more, and 10 parts by weight or less, 5 parts by weight or less, or 0.1 parts by weight or less, based on 100 parts by weight of adipic acid in the monomer mixture.
[0065] After the catalyst is added, a heat stabilizer can be added, which can suppress discoloration of the final PBAT.
[0066] Specifically, 0.001 to 1 part by weight of a heat stabilizer can be added based on 100 parts by weight of adipic acid in the monomer mixture.
[0067] For example, based on 100 parts by weight of adipic acid in the monomer mixture, the heat stabilizer may be added in an amount of 0.001 parts by weight or more, 0.005 parts by weight or more, 0.08 parts by weight or more, or 0.01 parts by weight or more, and 1 part by weight or less, 0.6 parts by weight or less, 0.3 parts by weight or less, or 0.1 parts by weight or less.
[0068] During polymerization of the prepolymer, the method may include a step of increasing the temperature of a reactor containing the prepolymer until the temperature reaches a range of 150 to 350° C.; after the increase in temperature, reducing the pressure of the reactor until the pressure reaches 0.1 to 0.00001 atm; and, after the reduction in pressure, maintaining the pressure and temperature to terminate the reaction after 2 to 8 hours.
[0069] For example, the temperature of the reactor containing the prepolymer can be increased until it reaches a temperature range that is 150°C or more, 170°C or more, 190°C or more, or 210°C or more, and 350°C or less, 320°C or less, 290°C or less, or 250°C or less.
[0070] One to ten minutes after reaching the temperature range, the pressure in the reactor can be reduced to a pressure range of 0.00001 atm or more, 0.00005 atm or more, 0.0001 atm or more, or 0.0002 atm or more, and 0.1 atm or less, 0.05 atm or less, 0.03 atm or less, or 0.01 atm or less.
[0071] After the reduction in pressure, the pressure and temperature are maintained to carry out the reaction, and the reaction can be terminated after 2 hours or more, 2.2 hours or more, 2.4 hours or more, or 3 hours or more and 8 hours or less, 7.5 hours or less, 7 hours or less, or 6 hours have elapsed since the start of the reaction.
[0072] Biodegradable polymer composite In another embodiment of the present invention, there is provided a biodegradable polymer composite comprising: a) polybutylene adipate terephthalate comprising repeating units derived from 1,4-butanediol, b) repeating units derived from adipic acid, and c) repeating units derived from terephthalic acid; and an organic filler dispersed among the polymer chains of the polybutylene adipate terephthalate.
[0073] The composite of the embodiment is produced by the production method of the embodiment described above, and can exhibit sufficient physical properties even when used alone without performing a post-process such as mixing with a reinforcing material.
[0074] In addition, the degree of crystallinity can be controlled according to the content of the organic filler, and biodegradability can be improved.
[0075] In the case of the biodegradable polymer composite according to one embodiment of the present invention, the acid value is at the same level as that of a biodegradable polymer polymerized in an environment in which no organic filler is present, and the acid value may be 1.8 to 3 mg KOH / g according to DIN EN 12634. For example, the acid value of the composite according to DIN EN 12634 may be 1.8 mg KOH / g or more and 3 mg KOH / g or less, 2.6 mg KOH / g or less, or 2.5 mg KOH / g or less.
[0076] Acid value is the number of milligrams of KOH required to neutralize the free fatty acids contained in 1 g of fat or oil. RCOOH+KOH→RCOOK+H2O, that is, acid value measures the amount of free fatty acids that are not in a bonded form and are in the form of glycerides.
[0077] In particular, in the esterification reaction, it is a measure of the degree of reaction and means the amount of KOH required to neutralize the carboxyl group contained in 1 g of polymer. A larger value indicates a lower reaction rate.
[0078] Here, the acid value can be measured according to DIN EN 12634. Specifically, a sample is dissolved in a mixed solution of O-cresol and chloroform in a weight ratio of 1:1, and 1 to 2 drops of an aqueous solution in which 0.1 wt % phenol red is dissolved are used as an indicator. A 0.1N potassium hydroxide (KOH) / ethanol solution is titrated using a micropipette, and the acid value can be measured according to the following formula 1.
[0079] [Formula 1] Acid value (mgKOH / g)=(V-V0)×M×F×1000 / W V: Volume (mL) of KOH / Ethanol solution consumed in titrating the sample V0: Volume (mL) of KOH / Ethanol solution consumed in the titration of the blank test M: Molar concentration of KOH / Ethanol solution (0.1M / L) W: mass of sample (g) F: Potency of KOH / Ethanol solution
[0080] The biodegradable polymer composite according to an embodiment of the present invention may have a crystallinity of 20 to 27% as measured using a differential scanning calorimeter. Within this range, regardless of the type of organic filler, as the content of the organic filler increases, the crystallinity may decrease and the biodegradability may increase.
[0081] The degree of crystallinity can be calculated as the weight fraction of the crystalline portion relative to the entire resin. The higher the degree of crystallinity (i.e., the more crystals there are), the stronger the polymer tends to be, and it is a factor that can predict strength. In particular, in the case of biodegradable polyester resins, it is known that the higher the degree of crystallinity, the lower the biodegradability, and it is a factor that can roughly predict biodegradability.
[0082] In the biodegradable polymer composite of one embodiment, unlike PBAT polymerized in an environment in which an organic filler is not present, the crystals may not grow completely due to steric hindrance caused by the organic filler during the crystallization process of molten PBAT upon cooling, resulting in low crystallinity.
[0083] Here, the crystallinity can be measured using a differential scanning calorimeter. Specifically, a differential scanning calorimeter (DSC, device name: DSC2500, manufacturer: TA instrument) is used to sequentially perform 1st heating, 1st cooling, and 2nd heating in a temperature range (-70 to 200 degrees, 10 degrees / min), and the crystallinity can be calculated (using PBAT ΔHm0=114 J / g) using the heat of fusion of the melting transition during the 2nd heating.
[0084] The biodegradable polymer composite of the embodiment has a tensile strength of 400 kgf / cm according to ASTM D 882. 2 ~550kgf / cm 2 It could be.
[0085] At this time, the MD tensile strength is 400-450kgf / cm 2 , specifically 410~450kgf / cm 2 , for example 410~430kgf / cm 2 TD tensile strength is 400-550kgf / cm 2 , specifically 430~550kgf / cm 2 , for example 430~500kgf / cm 2 It could be.
[0086] The tensile strength (max stress) can be measured by preparing a blown film test piece from a molded article containing the biodegradable polymer composite, and measuring it according to ASTM D 882. Specifically, a tensile test can be performed on each film test piece at a stretching speed of 10 mm / min using an Instron Universal Testing Machine (UTM), to measure the tensile strength.
[0087] The tensile test conditions are Load Cell 10KN, LE position 40mm, and the maximum stress of the SS curve can be measured for the machine direction (MD) and transverse direction (TD) respectively.
[0088] The polybutylene adipate terephthalate in the biodegradable polymer composite of one embodiment may contain 150 to 250 parts by weight of the repeating unit derived from 1,4-butanediol and 50 to 150 parts by weight of the repeating unit derived from terephthalic acid, based on 100 parts by weight of the repeating unit derived from adipic acid.
[0089] If the 1,4-butanediol content is excessively high, it is effective in increasing the esterification reaction rate, but there is a limit to how much the molecular weight of the polymer can be increased, and the amount of THF generated by side reactions increases, so it is less efficient from an economical standpoint. Also, if the input ratio of terephthalic acid to adipic acid is high, processability and biodegradability may decrease.
[0090] For example, the polybutylene adipate terephthalate in the biodegradable polymer composite of one embodiment may contain 180 to 220 parts by weight of the repeating unit derived from 1,4-butanediol and 80 to 120 parts by weight of the repeating unit derived from terephthalic acid, based on 100 parts by weight of the repeating unit derived from adipic acid.
[0091] The biodegradable polymer composite of the embodiment may contain 0.001 to 10 parts by weight of an organic filler based on 100 parts by weight of the repeating unit derived from adipic acid in the polybutylene adipate terephthalate.
[0092] Molded product In yet another embodiment of the present invention, there is provided a molded article comprising the biodegradable polymer composite described above.
[0093] The use of the molded article of the embodiment is not particularly limited, but it can be widely used in food wrapping paper, bottles, films, sheets, etc., where transparency is particularly required.
[0094] Hereinafter, the present invention will be described in more detail with reference to examples according to the present invention. However, such examples are presented as examples of the invention only and do not define the scope of the invention.
[0095] Preparation of the catalyst mixture Comparative Example 1 Titanium butoxide (0.5 mmol) and 1,4-butanediol (6.77 mol) were mixed and left at 160°C for 60 minutes to obtain a catalyst mixture.
[0096] Example 1 0.5 mmol of titanium butoxide, 0.847 g of cellulose, and 6.77 mol of 1,4-butanediol were mixed and reacted at 160° C. for 60 minutes to obtain a catalyst mixture in which 1,4-butanediol and an organic filler were dispersed.
[0097] Example 2 0.5 mmol of titanium butoxide, 8.47 g of cellulose, and 6.77 mol of 1,4-butanediol were mixed and reacted at 160° C. for 60 minutes to obtain a catalyst mixture in which 1,4-butanediol and an organic filler were dispersed.
[0098] Example 3 0.5 mmol of titanium butoxide, 0.847 g of starch, and 6.77 mol of 1,4-butanediol were mixed and reacted at 160° C. for 60 minutes to obtain a catalyst mixture in which 1,4-butanediol and an organic filler were dispersed.
[0099] Example 4 0.5 mmol of titanium butoxide, 8.47 g of starch, and 6.77 mol of 1,4-butanediol were mixed and reacted at 160° C. for 60 minutes to obtain a catalyst mixture in which 1,4-butanediol and organic filler were dispersed.
[0100] Prepolymer Production A monomer mixture containing 303 g of adipic acid, 317 g of terephthalic acid, and 0.88 g of glycerol, and the catalyst mixture of the above examples and comparative examples were added to the reactor.
[0101] The temperature of the reactor containing the reactants was maintained at 230° C., and nitrogen gas was introduced at a flow rate of 2 cc / min for 240 minutes to remove by-products, thereby producing a prepolymer.
[0102] Comparative Example 2 Prepolymer Production 610g of 1,4-butanediol, 0.847g of cellulose, 303g of adipic acid, 317g of terephthalic acid, 0.88g of glycerol, and 0.17g of titanium butoxide were added to the reactor, and the temperature of the reactor was maintained at 230°C. Then, nitrogen gas was introduced at a flow rate of 2cc / min for 240 minutes to remove by-products, and a prepolymer was produced.
[0103] Comparative Example 3 Prepolymer Production 610g of 1,4-butanediol, 8.47g of cellulose, 303g of adipic acid, 317g of terephthalic acid, 0.88g of glycerol, and 0.17g of titanium butoxide were added to the reactor, and the temperature of the reactor was maintained at 230°C. Then, nitrogen gas was introduced at a flow rate of 2cc / min for 240 minutes to remove by-products, and a prepolymer was produced.
[0104] Fabrication of biodegradable polymer composites 0.5 mmol of titanium butoxide as a catalyst was added to the reactor in which the prepolymer was prepared, and the mixture was stirred at 60 rpm for 10 minutes.
[0105] After the stirring, 0.09 g of a heat stabilizer (triethylphosphonoacetate) was added, and the mixture was stirred at 60 rpm for 10 minutes.
[0106] Then, the temperature of the reactor was raised to 240°C, and 5 minutes after the temperature reached 240°C, the internal pressure of the reactor was reduced to 0.001 atm, and polymerization was carried out while maintaining the reduced pressure and continuing stirring at 60 rpm. After 210 minutes from the start of polymerization, stirring was stopped and the reactor was disassembled to finally obtain a biodegradable polymer composite.
[0107] Measurement of weight average molecular weight The measurement target was dissolved in chloroform at a concentration of 1 mg / ml, and the solution was then put into a gel permeation chromatography (GPC) (PL GPC220, Agilent Technologies) instrument to measure the molecular weight. At this time, polystyrene was used as the standard polymer.
[0108] Acid Number Measurement The sample was dissolved in a 1:1 weight ratio O-cresol:chloroform mixture, and 1-2 drops of 0.1 weight % phenol red in water were used as an indicator.
[0109] A 0.1N potassium hydroxide (KOH) / ethanol solution was titrated using a micropipette to measure the acid value according to the following formula 1.
[0110] [Formula 1] Acid value (mg KOH / g)=(V-V0)×M×F×1000 / W V: Volume (mL) of KOH / Ethanol solution consumed in titrating the sample V0: Volume (mL) of KOH / Ethanol solution consumed in the titration of the blank test M: Molar concentration of KOH / Ethanol solution (0.1M / L) W: mass of sample (g) F: Potency of KOH / Ethanol solution
[0111] Acid value is the number of milligrams of KOH required to neutralize the free fatty acids contained in 1 g of fat or oil. RCOOH+KOH→RCOOK+H2O, that is, acid value measures the amount of free fatty acids that are not in a bonded form and are in the form of glycerides.
[0112] In particular, in the esterification reaction, it is a measure of the degree of reaction and means the amount of KOH required to neutralize the carboxyl group contained in 1 g of polymer. A larger value indicates a lower reaction rate.
[0113] [Table 1]
[0114] In the comparative examples and examples, the acid value and weight average molecular weight, which can determine the tendency of the polymerization reaction, were almost at the same level.
[0115] Evaluation of crystallinity and mechanical properties The crystallinity and mechanical properties of the biodegradable polymer composites according to the examples and comparative examples were measured, and the results are summarized in the following table.
[0116] Specifically, the method for measuring the crystallinity is as follows.
[0117] Crystallinity: For the biodegradable polymer composites of Examples 1 to 4 and the PBATs of Comparative Examples 1 to 3, a first heating, a first cooling, and a second heating were sequentially performed in a temperature range (-70 to 200°C, 10°C / min) using a Differential Scanning Calorimeter (DSC, device name: DSC2500, manufacturer: TA Instruments), and the crystallinity was calculated using the heat of fusion of the melting transition during the second heating (PBAT ΔHm0=114 J / g).
[0118] Preparation of test specimens: The biodegradable polymer composites of the examples and comparative examples were each blown into a blown film by inflation molding using a single screw extruder (SHINHWA Industrial Single Screw Extruder, Blown Film M / C, 50mm, L / D=20) at an extrusion temperature of 130°C to 170°C to a thickness of about 50μm. At this time, the die gap was 2.0mm and the blown-up ratio was 2.3.
[0119] Tensile strength (max stress): Tensile strength was measured by performing a tensile test on each film specimen at a stretching speed of 10 mm / min using an Instron Universal Testing Machine (UTM) according to ASTM D 882. The tensile test conditions were Load Cell 10KN, LE position 40 mm, and the maximum stress of the SS curve was measured for the machine direction (MD) and transverse direction (TD).
[0120] [Table 2]
[0121] The degree of crystallinity can be calculated as the weight fraction of the crystalline portion relative to the entire resin. The higher the degree of crystallinity (i.e., the more crystals there are), the stronger the polymer tends to be, and it is a factor that can predict strength. In particular, in the case of biodegradable polyester resins, it is known that the higher the degree of crystallinity, the lower the biodegradability, and it is a factor that can roughly predict biodegradability.
[0122] The PBAT of the comparative example had a crystallinity of about 29% to about 34%, and the biodegradable polymer composites of Examples 1 to 4 containing organic fillers tended to have slightly reduced crystallinity values compared to the comparative example.
[0123] The reason why the crystallinity value in the examples of the present invention was slightly lower than that in the comparative examples is that the crystals could not grow completely due to steric hindrance caused by the organic filler during the crystallization process of the molten PBAT by cooling.
[0124] Also, a small decrease in crystallinity may mean a small increase in biodegradability. In Examples 1 to 4, which contain organic fillers, it can be seen that the crystallinity decreased more as the content of the organic filler increased, regardless of the type of organic filler. This shows that the crystallinity and biodegradability can be controlled by adjusting the content of the organic filler.
[0125] In addition, the biodegradable polymer composites of Examples 1 to 4, which contained an organic filler, exhibited significantly increased MD and TD tensile strengths compared to the PBAT of the Comparative Example.
[0126] In particular, in Examples 1 to 4, there was a tendency that the MD and TD tensile strengths increased as the content of the organic filler increased, regardless of the type of organic filler.
[0127] This tendency is believed to be due to the fact that the amorphous portion increases relatively as the crystallinity decreases.
[0128] summary With reference to the trends of Examples 1 to 4, the biodegradability and mechanical properties of the biodegradable polymer composite can be controlled within the desired range by adjusting the content of the organic filler.
[0129] However, this is merely an example, and as long as the above-described series of steps are used, a biodegradable polymer composite that exhibits sufficient physical properties even when used alone without performing post-processing and has improved biodegradability, unlike polybutylene adipate terephthalate polymerized in an environment in which no organic filler is present, can be provided efficiently and at low cost.
Claims
1. preparing a monomer mixture comprising adipic acid and terephthalic acid; mixing an organic filler, 1,4-butanediol, and a catalyst to produce a catalyst mixture; and mixing the monomer mixture with the catalyst mixture to carry out an esterification reaction; The organic filler is at least one selected from the group consisting of cellulose and starch-based compounds, The organic filler in the catalyst mixture is contained in an amount of 0.01 to 10 parts by weight based on 100 parts by weight of adipic acid in the monomer mixture.
2. 2. The method for producing a biodegradable polymer composite according to claim 1, wherein the 1,4-butanediol in the catalyst mixture is contained in an amount of 150 to 250 parts by weight based on 100 parts by weight of adipic acid in the monomer mixture.
3. The method for producing a biodegradable polymer composite according to claim 1 or 2, wherein the catalyst in the catalyst mixture is contained in an amount of 0.001 to 10 parts by weight based on 100 parts by weight of adipic acid in the monomer mixture.
4. The method for producing a biodegradable polymer composite according to any one of claims 1 to 3, wherein the organic filler in the catalyst mixture is contained in an amount of 0.5 to 20 g per 1 mmol of the catalyst.
5. The method for producing a biodegradable polymer composite according to any one of claims 1 to 4, wherein the monomer mixture contains 50 to 150 parts by weight of the terephthalic acid based on 100 parts by weight of the adipic acid in the monomer mixture.
6. The catalyst is The method for producing a biodegradable polymer composite according to any one of claims 1 to 5, wherein the titanium oxide is at least one selected from the group consisting of titanium methoxide, titanium ethoxide, titanium propoxide, titanium isopropoxide, titanium butoxide, and titanium isobutoxide.
7. The step of carrying out the esterification reaction comprises: preparing a prepolymer; and The method for producing a biodegradable polymer composite according to claim 1 , further comprising the step of polymerizing the prepolymer to obtain a biodegradable polymer composite.
8. During polymerization of the prepolymer, The method for producing a biodegradable polymer composite according to claim 7, wherein 0.001 to 10 parts by weight of the catalyst is additionally added based on 100 parts by weight of the adipic acid in the monomer mixture.
9. a) polybutylene adipate terephthalate comprising repeat units derived from 1,4-butanediol, b) adipic acid, and c) terephthalic acid; and an organic filler selected from the group consisting of cellulose and starch-based compounds dispersed among the polymer chains of the polybutylene adipate terephthalate; A biodegradable polymer composite having a crystallinity of 20-27% as measured by differential scanning calorimetry.
10. Tensile strength value measured according to ASTM D 882 is 400 kgf / cm 2 ~550kgf / cm 2 The biodegradable polymer composite according to claim 9,
11. A molded article comprising the composite of claim 9 or 10.
Citation Information
Patent Citations
Polymerizable Macrocyclic Oligomer Masterbatch Containing Dispersed Fillers
JP2008503613A
Nanocrystalline cellulose (NCC) and polylactic acid (PLA) nanocomposite biomaterial
JP2013519736A
Production method of aliphatic aromatic polyester
JP2018145413A
Polymer compositions for highly degradable films
JP2020511565A
Biodegradable polyester resin composition, nonwoven fabric and film, as well as its manufacturing method
JP2021188038A